Corporate image and a sport’s governing body - Sekhon, Harjit; Roy, Sanjit Kumar; Chadwick, Simon; Devlin, James (Taylor & Francis, 2016)
This study provides a topical examination of corporate image and a sport’s governing body. Our study is based on 500 worldwide followers of football and has major implications because it serves as a basis for understanding how sports fans might develop and maintain trust in a governing body, and what the attendant antecedents and consequences are. The evidence from our research shows that the key attribute that enables a sport’s governing body to build trust is corporate image; corporate image is different to corporate reputation because it is built on mental imagery rather than value judgements. This finding, we argue, is also applicable to other sports’ governing bodies, particularly when there is a need to repair or re-build trust. The management of corporate image, as a mental image, is particularly significant if a sport’s governing body’s corporate image is called into question because income streams may be undermined.